2014
DOI: 10.3390/molecules191016058
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Sar Study of Diarylpentanoid Analogues as New Anti-Inflammatory Agents

Abstract: A series of ninety-seven diarylpentanoid derivatives were synthesized and evaluated for their anti-inflammatory activity through NO suppression assay using interferone gamma , which demonstrated the most significant NO suppression activity with IC50 values of 4.9 ± 0.3 µM and 9.6 ± 0.5 µM, respectively. A structure-activity relationship (SAR) study revealed that the presence of a hydroxyl group in both aromatic rings is critical for bioactivity of these molecules. With the exception of the polyphenolic derivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…The NO inhibition assay was performed as previously reported by Leong et al, with slight modification. Each sample was prepared at a concentration of 1000 μg/mL in well.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The NO inhibition assay was performed as previously reported by Leong et al, with slight modification. Each sample was prepared at a concentration of 1000 μg/mL in well.…”
Section: Methodsmentioning
confidence: 99%
“…The 3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide (MTT) cell viability assay was conducted according to the method optimised by Leong et al . with slight modification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22][23] Unlike curcumin, diarylpentanoids are chemically stable at physiological pH and metabolically stable in rat liver microsomes, which make them the most impactful candidates among curcuminoids deserving further intensive investigations towards developing novel bioactive molecules with good stability and bioavailability Previously, we have shown that α,β-unsaturated β-diketone and cyclohexanone fragments are crucial for diarylpentanoids' bioactivities in different studies. 15,26 In continuing our effort on the search of new anti-inflammatory agent, we have now synthesized a series of 2-benzoyl-6-benzylidenecyclohexanone analogues, a novel family of diarylpentanoid which incorporated the integration of α,β-unsaturated β-diketone and cyclohexanone moieties. As represented in Scheme 1, compounds 1-24 (III) were successfully synthesized through a series of reactions, which involved benzoylation of cyclohexanone and aldol condensation with aryl aldehydes.…”
mentioning
confidence: 99%
“…[34] [35] In this work, the NO inhibition activity of 6 and 7 was evaluated in IFN-c/LPS-stimulated RAW264.7 macrophages and compared with the initial drug. It responds to these threats by secreting proinflammatory mediators.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%